[PP.23.10] CASE REPORT: PREGNANCY OUTCOMES IN A HYPERTENSIVE WOMAN TREATED WITH VALSARTAN UNTIL 8 WEEKS OF GESTATION. (September 2017) - Wojciechowska, E.; Gryglas, P.; Jedrusik, P.; Wielgos, M.; Gaciong, Z.
Abstract : Objective: We evaluated pregnancy outcomes, fetal growth, and the effect of serial ambulatory blood pressure monitoring (ABPM) on pregnancy safety in a hypertensive woman treated with valsartan until 8 weeks of gestation. Design and method: A 42-year-old Caucasian woman with hypertension for about 5 years, without any history of cardiovascular disease, diabetes and renal disease, presented with an unplanned pregnancy conceived during regular antihypertensive therapy. Her previous pregnancy was delivered by caesarean section due to preeclampsia. The current pregnancy was diagnosed at 8 weeks and the patient was treated with valsartan (160 mg/d) until that time. Blood pressure (BP) at the initial visit was 170/100 mmHg. Physical examination was unremarkable. Valsartan was stopped, and methyldopa 1500 mg/d and acetylsalicylic acid 75 mg/d were initiated. Labetalol 100 mg/d was added at 14 weeks. The initial ultrasound at 12 weeks revealed a living fetus with heart rate of 164 bpm, crown-rump length of 65.8 mm, and nuchal translucency of 2.2 mm, posterior placenta, and normal amniotic fluid. Markers of chromosomal abnormalities suggested nasal bone maldevelopment. Apart from this, fetal anatomy was normal. Results: Serial ABPM was performed every 3 weeks throughout the pregnancy, allowing stable normal BP values on labetalol 200 mg/d and methyldopa 2000 mg/d. Follow-up ultrasound studies did not show any defects within the viscerocranium, neural tube, kidneys, and the heart. Previously suspected lack of nasal bone was not confirmed. A healthy boy (length 57 cm, body weight 3960 g) was delivered at 39 weeks by cesarean section due to fetal malpresentation and history of previous cs. Conclusions: Valsartan therapy during the first 8 weeks of pregnancy did not affect fetal development and condition of the neonate. Serial ABPM allowed adequate BP control throughout the pregnancy without development of preeclampsia.